Seattle (WA, USA), Museum of Pop Culture, Fassade – 2022 – 1588 - Dietmar Rabich (Wikimedia Commons, 2022)
Notice iconographique issue de Wikimedia Commons. Titre: Seattle (WA, USA), Museum of Pop Culture, Fassade – 2022 – 1588. Part of the facade of the Museum of Pop Culture in Seattle, Washington, USA
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons